PENGEMBANGAN MODEL PEMBELAJARAN BERORIENTASI KKNI YANG MELIBATKAN KECERDASAN EMOSIONAL - Binur Panjaitan; Hulman Sihombing; Oktober Tua Aritonang; Betty A.S. Pakpahan; Rafita Tioria Sianipar (Jurnal Dinamika Pendidikan, 2020)
The root of the problem in this study is the fact that student learning achievement is less satisfying, and learning that has occurred so far does not involve emotional intelligence. The problem in this study is "how is the process and results of developing a learning model that involves the emotional quotien of qualified lecturers and students?" The purpose of this study is to obtain a quality learning model (valid, effective and practical) through a development process. The development phases used are: the initial investigation phase, the development phase, the realization phase and the testing, evaluation and revision phase. In Trial I (subject 35 people), the learning model was not effective, not yet practical even though it was valid, so it was revised. After the learning model was revised, another trial II was conducted. In Trial II (subject 38 people), the learning model was still not effective and practical so it was revised again. After the learning model was revised, trial III was conducted. In Trial III (bubject 38 people), a quality learning model was obtained with syntax: (1) emotional apperception, (2) construction of knowledge, (3) independent practice and (4) recitation. One of the results obtained in this study is that learning using the developed learning model has an impact on the achievement of student learning completeness.